Airway complications in lung transplant recipients with telomere‐related interstitial lung disease. Issue 3 (13th December 2021) - Choi, Bina; Messika, Jonathan; Courtwright, Andrew; Mornex, Jean François; Hirschi, Sandrine; Roux, Antoine; Le Pavec, Jérôme; Quêtant, Sébastien; Froidure, Antoine; Lazor, Romain; Reynaud‐Gaubert, Martine; Borgne, Aurélie Le; et al.
Abstract: Introduction: Patients with short telomere‐related interstitial lung disease (ILD) have worse outcomes after lung transplantation. We hypothesized that post‐transplant airway complications, including dehiscence and bronchial stenosis, would be more common in the short telomere ILD lung transplant population. Methods: We conducted a multi‐institutional (Brigham and Women's Hospital, Groupe de Transplantation de la SPLF) retrospective cohort study of 63 recipients between 2009 and 2019 with ILD and short telomeres, compared to 4359 recipients from the Scientific Registry of Transplant Recipients with ILD and no known telomeropathy. Results: In the short telomere cohort, six recipients (9.5%) developed dehiscence and nine recipients (14.3%) developed stenosis, compared to 60 (1.4%) and 149 (3.4%) in the control, respectively. After adjusting for age, sex, and bilaterality, the presence of short telomeres was associated with higher odds of dehiscence (odds ratio (OR) = 8.24, 95% confidence interval (CI) = 3.34 20.29, p < .001) and stenosis (OR = 4.63, 95% CI 2.21 9.69, p < .001). Conclusion: The association between the presence of short telomeres and post‐transplant dehiscence and stenosis suggest that airway complications may be a contributor to increased morbidity and mortality in patients with telomere‐related ILD.